PENDIDIKAN LITERASI MEDIA TENTANG UJARAN KEBENCIAN DI KALANGAN ORMAS PEREMPUAN - Eka Nada Shofa Alkhajar; Sri Herwindya Baskara Wijaya; Firdastin Ruthnia Yudiningrum; Agusniar Rizka Luthfia; Pawito Pawito; Hamid Arifin (LPPM Universitas PGRI Adi Buana Surabaya, 2023)
Hate speech is one of the serious problems related to the presence of the internet, particularly social media. Media literacy education on hate speech is one of the efforts to overcome the problem. This community service was held in Klaseman Village, Sukoharjo. It aims to increase the community service target’s media literacy on hate speech. The community service target is expected to be able to access the internet wisely and avoid the practice of hate speech. The result achieved from the community service is that the target of community service had the knowledge and skills to prevent and counter the spread of hate speech on the internet.